Measurement of melamine migration from melamine-ware products by designed HPLC method and the effect of food-type on the level of migration - Haghi, Ehsan (Interdiscip Toxicol, 2018)
Melamine-ware is widely used around the world. There is a public health concern as regards the safety of melamine when exposed to food. This study was carried out to measure the level of melamine migration in melamine-ware products by HPLC method and the effect of food-type on the level of melamine migration. In food control laboratories in Iran, there is no common method to measure and monitor melamine migration, hence a method using HPLC technique was adopted and validated to solve this problem. The validation results showed the reliability with 94.9% accuracy and 95.3% precision. Furthermore, the limit of detection (LOD) and quantification (LOQ) were 0.145 and 0.435 μg/ml, which for a new method were within acceptable ranges. Melamine migrations from 4 most available melamine wares were measured. Distilled water, 3% acetic acid and 15% ethanol were used as food simulant at 30 °C for 90 min. Although melamine migration occurred in all samples and acidic conditions had a significant effect, the values were not higher than the European standard (30 μg/ml). The study revealed that the HPLC method was valid and could be applied and developed to measure melamine migration. However, precautions should be considered while choosing melamine-ware utensil as long-term exposure to this substance has a negative effect on health, especially on the kidneys.